2005
DOI: 10.1080/03014460500075118
|View full text |Cite
|
Sign up to set email alerts
|

Genetic disorders in a paediatric hospital in Cambodia

Abstract: Cambodia is an extremely underdeveloped country in Southeast Asia with a childhood mortality rate of 105/1000 live births. Angkor Hospital for Children is a paediatric teaching hospital in Siem Reap, northwest Cambodia, which serves as the provincial paediatric department but also sees children from provinces throughout northern Cambodia, and with training provided for health workers from all parts of the country. The impact of genetic disease on this paediatric population is discussed, addressing the areas of… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2010
2010
2013
2013

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 0 publications
0
3
0
Order By: Relevance
“…Visual loss was present since birth in 74.2% (46) and occurred in the first year of life in 11.3% (7). Family history of eye disease was found in 37.1% (23), with the majority of these having cataract (11,47.8%) and retinal dystrophy (5, 21.7%). A history of consanguineous marriage was present in 17.7% (11) and accounted for 43.5% (10) …”
Section: Resultsmentioning
confidence: 98%
See 1 more Smart Citation
“…Visual loss was present since birth in 74.2% (46) and occurred in the first year of life in 11.3% (7). Family history of eye disease was found in 37.1% (23), with the majority of these having cataract (11,47.8%) and retinal dystrophy (5, 21.7%). A history of consanguineous marriage was present in 17.7% (11) and accounted for 43.5% (10) …”
Section: Resultsmentioning
confidence: 98%
“…It is favored to varying degrees in Cambodia, but there are currently no reliable data on its prevalence. 23 Health education and genetic counseling have been shown to be effective in preventing recessive diseases such as thalassaemia in some populations, 24 but a WHO expert group has concluded that an attempt to discourage consanguineous marriage on genetic grounds might do more harm than good. 25 The proportion of hereditary disease in this study is one of the highest reported and is similar to studies from Indonesia (41.5%).…”
Section: Discussionmentioning
confidence: 99%
“…There are anecdotal reports of blackwater fever and some deaths. In addition, children presented to one paediatric referral hospital with blackwater fever following the ingestion of traditional medicines, sulphonamides and anti-malarial drugs [55]. Mass treatment has been used in Cambodia, which included a 9 mg dose of primaquine [56].…”
Section: Introductionmentioning
confidence: 99%